Nabopolassar's Restoration Work on the Wall Im-gur-Enlil at Babylon - al-Rawi, Farouk N. H.
copies (A Babylon 11, BM 26263 = 98-5-14,81, A Babylon 12, A Babylon 4, A Babylon 6, A Babylon 7), photo (A Babylon 10-12)